Foods of Plant Origin - Netzel, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
It is now well accepted that the consumption of plant-based foods is beneficial to human health. Fruits, vegetables, grains, and derived products can be excellent sources of minerals, vitamins, and fiber and usually have a favorable nutrient-to-energy ratio. Furthermore, plant foods are also a rich source of phytochemicals such as polyphenols, carotenoids, and betalains, with potential health benefits for humans. Many epidemiological studies have made a direct link between the consumption of plant foods and health. Human intervention studies have also shown that higher intake/consumption of plant foods can reduce the incidence of metabolic syndrome and other chronic diseases, especially in at-risk populations such as obese people. In addition to its health benefits, plant foods are also used as functional ingredients in food applications such as antioxidants, antimicrobials, and natural colorants. The Special Issue "Foods of Plant Origin" covers biodiscovery, functionality, the effect of different cooking/preparation methods on bioactive (plant food) ingredients, and strategies to improve the nutritional quality of plant foods by adding other food components using novel/alternative food sources or applying non-conventional preparation techniques.